Peningkatan Kinerja Guru Mata Pelajaran melalui Penerapan Model Pembelajaran Kooperatif berbasis kegiatan Suvervisi Pada Siswa - Simson Selutan (ILIN Institute Makassar, 2020)
The research aims to determine (1) the ability of subject teachers to prepare lesson plans for cooperative learning models; (2) The ability of the teacher to apply the cooperative learning model. This research method is a type of school action research which is an action research, the implementation uses two cycles consisting of planning, implementation, observation and reflection stages involving 4 teachers of SMAN 1 Krayun. The results showed (1) there was a significant improvement in the ability of teachers in preparing lesson plans for cooperative learning models starting in the pre-cycle 62.55% with the low category, 81% in the first cycle in the good category, and 95.5% in the second cycle with the very good category; (2) There was an increase in the teacher's ability to apply the cooperative learning model from the pre-cycle with a percentage of 56% in the low category, 73% in the first cycle in the good category, 92.5% in the second cycle in the very good category with 100% learning completeness. The results show that with supervision through guidance, coaching in applying the cooperative learning model to teachers, has an impact on student performance and achievement.